The impact of human resource management practices on operational performance: recognizing country and industry differences - Ahmad, Sohel; Schroeder, Roger G. (Journal of Operations Management, 2003)
AbstractThe interest in strategic human resource management (HRM) has spawned a number of empirical research studies that investigated the impact of HRM practices on organizational performance. However, very little attention has been paid to address the impact of HRM practices on operations management and to generalize the findings across countries and industries. Success of some business decisions (e.g. globalization and merger and acquisition) necessitates recognition and reconciliation of the differences among HRM practices in different countries and industries. This study attempts to generalize the efficacy of seven HRM practices proposed by Pfeffer in the context of country and industry, focusing primarily on the effects of these practices on operations. The findings provide overall support for Pfeffer’s seven HRM practices and empirically validate an ideal‐type HRM system for manufacturing plants.